Productivity in the Non-Oil Sector in Nigeria : Firm-Level Evidence - Herrera, Santiago; Kouame, Wilfried (World Bank, Washington, DC, 2017)
This paper examines the determinants of the productivity of Nigerian firms, using three waves of Enterprise Surveys from 2007, 2009, and 2014 and 7,670 firms. The paper uses three alternative measures of productivity, which are found to be highly correlated: labor productivity, value added per worker, and total factor productivity. The more notable trends in the data show: a rise in productivity, with the output of exporting firms decreasing; increasing concentration of production, reflected in the rise of the Herfindahl-Hirschman index by a factor of three; increasing costs of crime, power outages, lack of security, and bribery; significant heterogeneity of these costs along several dimensions, such as firm size, age, location, and the exporting or domestic nature of the market it serves. These costs are inversely related with investment. Regardless of the measure of productivity, its main determinants are the education of the worker, size of the firm, availability of credit, and business climate variables. When labor productivity is used, the stock of capital is also a major determinant of productivity. Within the investment climate variables, power outages and the corruption index are the more significant ones. Power outages are negatively associated with productivity. Bribery is positively related, supporting the "greasing the wheels" hypothesis of bribery as a factor that reduces transaction costs. The impact is nonlinear, as it decreases with firm size. The results also show a positive association between productivity and exporting, but the causality is reversed when the analysis controls for endogeneity: productivity is a weak determinant of the likelihood of a firm becoming an exporter.